Treatment of asymptomatic UTI in older delirious medical in-patients: A prospective cohort study. (September 2017) - Dasgupta, Monidipa; Brymer, Chris; Elsayed, Sameer
Highlights: Asymptomatic UTI is treated commonly in older medically ill individuals with delirium. Treating asymptomatic UTI was associated with worse outcomes after delirium. There was no evidence for benefit in treating asymptomatic UTI. Abstract: Background: Despite clinical practice guidelines, asymptomatic bacteriuria (ASB) in older people is frequently treated. A common reason for treating ASB is a change in mental status. Objective: To determine how often asymptomatic UTI is treated in older medically ill delirious individuals and its association with functional recovery. Methods: Consecutive older medical in-patients were screened for delirium, and followed in hospital. Treatment for asymptomatic UTI was defined as documented treatment for a possible urinary tract infection with antibiotics, without concurrent infectious or urinary symptoms. The primary outcome was functional recovery at discharge or 3 months post-discharge. Poor functional recovery was defined by any one of death, new permanent long-term institutionalization or decreased ability to perform activities of daily living. Results: The study sample comprised 343 delirious in-patients, of which 237 (69%) had poor functional recovery. Ninety two (27%) delirious in-patients were treated for asymptomatic UTI. Treatment for asymptomatic UTI was associated with poor functional recovery compared to other delirious in-patients (RR 1.30, 95% CI: 1.14–1.48 overall). Similar results were seen when the analysis was restricted to only bacteriuric delirious individuals. Seven (7.5%) individuals treated for asymptomatic UTI developed Clostridium difficile infection compared to eight (3.2%) in the remainder of the delirious cohort (OR 2.45, 95% CI: 0.86–6.96). Conclusions: These results suggest that treatment of asymptomatic UTI in older medical in-patients with delirium is common, and of questionable benefit. Further research is needed to establish guidelines to minimize over-treatment of UTI in older delirious in-patients.